2010
DOI: 10.1002/chem.200902883
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Reactivity of a [1],[1]Disilamolybdenocenophane

Abstract: The electronic structure of the two-fold bridged [1],[1]disilamolybdenocenophane has been analyzed by means of density functional theory. As predicted, the relatively high charge at the metal center and, in particular, the highly strained geometry determine a noticeable reactivity towards unsaturated organic substrates. Thus, treatment with the nonpolar reagents 2-butyne and azobenzene leads to side-on coordination of the substrate to the metal center, whereas the reaction with polar tert-butylisonitrile gives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…A two-electron-reduced azobenzene is further evinced by significant elongation of the diazo moiety (N13–N13′ = 1.440(3) Å) compared to neutral cis -azobenzene (1.251 Å) and related trans -isomers . The reduction of the N–N bond in 2-AzBz is comparable to those observed in transition metal and lanthanide complexes bearing an (η 2 -1,2-RNNR) 2– unit, including Cp*WMe 3 ­(η 2 -MeNNMe) (1.38(1) Å), Cp 2 Zr­(η 2 -PhNNPh)­(NC 5 H 5 ) (1.434(4) Å), (κ 2 -(η 5 -C 5 H 4 SiMe 2 ) 2 )­Mo­(η 2 -PhNNPh) (1.4061(9) Å), [Cp*­(THF)­Sm] 2 ­[N 2 Ph 2 ] 2 (1.44(1) Å), and [Cp 2 (THF)­Yb] 2 [N 2 Ph 2 ] 2 (1.470(6) Å) . Additionally, the N–N bond in 2-AzBz is significantly more reduced than the analogous bond in [((SiMe 2 NPh) 3 -tacn)­U­(η 2 -N 2 Ph 2 ) (1.353(4) Å) and Cp* 2 Sm­(N 2 Ph 2 )­(THF) (1.388(15) Å), both of which are characterized as containing a singly reduced, (PhNNPh) 1– , ligand.…”
Section: Resultsmentioning
confidence: 69%
“…A two-electron-reduced azobenzene is further evinced by significant elongation of the diazo moiety (N13–N13′ = 1.440(3) Å) compared to neutral cis -azobenzene (1.251 Å) and related trans -isomers . The reduction of the N–N bond in 2-AzBz is comparable to those observed in transition metal and lanthanide complexes bearing an (η 2 -1,2-RNNR) 2– unit, including Cp*WMe 3 ­(η 2 -MeNNMe) (1.38(1) Å), Cp 2 Zr­(η 2 -PhNNPh)­(NC 5 H 5 ) (1.434(4) Å), (κ 2 -(η 5 -C 5 H 4 SiMe 2 ) 2 )­Mo­(η 2 -PhNNPh) (1.4061(9) Å), [Cp*­(THF)­Sm] 2 ­[N 2 Ph 2 ] 2 (1.44(1) Å), and [Cp 2 (THF)­Yb] 2 [N 2 Ph 2 ] 2 (1.470(6) Å) . Additionally, the N–N bond in 2-AzBz is significantly more reduced than the analogous bond in [((SiMe 2 NPh) 3 -tacn)­U­(η 2 -N 2 Ph 2 ) (1.353(4) Å) and Cp* 2 Sm­(N 2 Ph 2 )­(THF) (1.388(15) Å), both of which are characterized as containing a singly reduced, (PhNNPh) 1– , ligand.…”
Section: Resultsmentioning
confidence: 69%
“…In the metallo-ylidenes the values were lower with Cr (−1.0) and Si (0.88), for Mo (−0.49) and Si (0.82), and for W (−0.34) and Si (0.82) . A DFT calculation addressed the electronic nature of [1],[1]-disilamolybdenocenophane and concluded that the complex was formulated consistent with the calculation results …”
Section: Bonding and Calculationsmentioning
confidence: 99%
“…352 A DFT calculation addressed the electronic nature of [1], [1]disilamolybdenocenophane and concluded that the complex was formulated consistent with the calculation results. 404 7.2.3. Fe, Ru, Os.…”
Section: Author Informationmentioning
confidence: 99%
“…To test the idea, we turned our attention towards the highly strained [1],[1]‐disilamolybdenocenophane ( 1 ) 9. In our hands, this particular complex proved to have three reactive centers, which are located at the central Mo and both Si atoms9, and are utilized in its reaction with tert ‐butylisonitrile to form the unprecedented ansa ‐Fischer‐type carbene complex 2 (Scheme ) 10…”
Section: Methodsmentioning
confidence: 99%